Innovation in Using the Quizizz-Assisted Zoom Application in Chemistry Learning during the Covid-19 Pandemic - Leony Sanga Lamsari Purba; Sali Afridika; Yohana Junita (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2021)
This study aims to determine the increase in learning outcomes using thequizizz-assisted zoom application in chemistry learning during the Covid-19pandemic. This research is quantitative research with a population of allstudents of SMA Pelita Kasih and the sample using the True Experimentalmethod takes the Pretest - Posttest Control Group Design. The analysis testwas carried out using paired t-test and n-gain score. The results showed anincrease in learning outcomes using the quizizz-assisted zoom application inchemistry learning during the Covid-19 pandemic with ttable (1.69) tcount (10.12)and sig 0.05 (df = 31). Gain test results were obtained by 54.68% in themedium category, so it can be concluded that learning with the Quizizzapplication is effective in improving cognitive abilities and encouragingstudents to interact and compete towards better competencies.